PERSEPSI MASYARAKAT TERHADAP KEBERADAAN VIDEOTRON SEBAGAI MEDIA PROMOSI DI UNIVERSITAS MUHAMMADIYAH PURWOKERTO - Jayanti, Dewi (Media Ekonomi, 2017)
This research aimed to find out the society’s perception towards the existence of videotron as a media of promotion in University of Muhammadiyah Purwokerto based on the Importance Analyze (IPA) method. This research used the attributes of the videotron which were size, color, message, zoning/placement and the effect of the videotron. It was a qualitative descriptive research. The attributes performance in quadrant A needed to be improved and evaluated periodically in order to know the society’s expectation. The attributes included in quadrant B were the attributes whose performance needed to be maintained because the society had been satisfied. The attributes included in quadrant C were the attributes which had low priority and ordinary performance. The attributes included in quadrant D were the attributes considered less important by the society but the performance of the videotron was very good. The results of the research showed that the level of suitability was 86.77% on the range of 81-100% which showed that society’s perception was “very good” towards the videotron as a media of promotion in University of MuhammadiyahPurwokerto.